Age Determination of Aborted Fetus in A Barbari Goat - Kumar Singh, Avaneesh; Kumar, Mahesh; Sachan, Vikas; Balamurugan, Balachandra; Kumar Ravi, Sanjay (The Indian Journal of Animal Reproduction, 2026)
The present communication describes the assisted per vaginal delivery of an aborted fetus in a newly purchased Barbari goat with an uncertain pregnancy status. The delivery was facilitated through manual cervical dilation, adequate lubri cation, and gentle traction. Gestational age was estimated based on crown–rump length (CRL) measurement. The dam recovered uneventfully following treatment.
Keywords: Abortion; Fetus; Gestational age; Goat